Morality, competition, and the firm : the market failures approach to business ethics - Heath, Joseph, 1967- (Oxford ; New York : Oxford University Press, USA, 2014)
"In this collection of provocative essays, Joseph Heath provides a compelling new framework for thinking about the moral obligations that private actors in a market economy have toward each other and to society. In a sharp break with traditional approaches to business ethics, Heath argues that the basic principles of corporate social responsibility are already implicit in the institutional norms that structure both marketplace competition and the modern business corporation. In four new and nine previously published essays, Heath articulates the foundations of a "market failures" approach to business ethics. Rather than bringing moral concerns to bear upon economic activity as a set of foreign or externally imposed constraints, this approach seeks to articulate a robust conception of business ethics derived solely from the basic normative justification for capitalism. The result is a unified theory of business ethics, corporate law, economic regulation, and the welfare state, which offers a reconstruction of the central normative preoccupations in each area that is consistent across all four domains. Beyond the core theory, Heath offers new insights on a wide range of topics in economics and philosophy, from agency theory and risk management to social cooperation and the transaction cost theory of the firm"--
Machine generated contents note: -- Acknowledgements -- Introduction -- Part 1: The Corporation and Society -- 1. A Market Failures Approach to Business Ethics -- 2. Stakeholder Theory, Corporate Governance and Public Management (with Wayne Norman) -- 3. Business Ethics Without Stakeholders -- 4. An Adversarial Ethic for Business: or, When Sun-Tzu met the Stakeholder -- 5. Business Ethics and the 'End of History' in Corporate Law -- Part 2: Cooperation and the Market -- 6. Contractualism: Micro and Macro -- 7. Efficiency as the Implicit Morality of the Market -- 8. The History of the Invisible Hand -- 9. The Benefits of Cooperation -- Part 3: Extending the Framework -- 10. The Uses and Abuses of Agency Theory -- 11. Business Ethics and Moral Motivation: a Criminological Perspective -- 12. Business Ethics After Virtue -- 13. Reasonable Restrictions on Underwriting -- Bibliography -- Index.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Business ethics; Profit -- Moral and ethical aspects; Competition; Corporations -- Moral and ethical aspects; Electronic books